The Effect of Fermentation Time and Mass Variation of Saccharomyces Cerevisiae on the Characteristics of Virgin Coconut Oil from the Fermentation Process of Coconut Milk - Anisa Tri Hutami; Evawanti A. Warsito (Sean Institute, 2023)
The many advantages of processed coconut products are shown by virgin coconut oil. Extraction, centrifugation, and fermentation are the three main methods for producing virgin coconut oil. In this experiment, baker's yeast (Saccharomyces cerevisiae) was used to ferment virgin coconut oil. The purpose of this research is to identify the properties of virgin coconut oil as a function of fermentation duration and mass variation of Saccharomyces cerevisiae. According to this research, separating the water from the milk of coconuts is the first step in producing virgin coconut oil. Fermentation lengths of 12, 18, and 24 hours are used to combine skimmed cream with Saccharomyces cerevisiae, with amounts ranging from 0 to 2 grammes. Iodine, peroxide, and acid quantities are then determined by analysing the virgin coconut oil that is produced. Research shows that while making virgin coconut oil from coconut milk, the amount of time yeast is left to ferment and the mass of Saccharomyces cerevisiae do not correlate with the iodine number. The peroxide number for all variables of fermentation duration and yeast mass is two meq/kg. The acid number tends to increase with the length of fermentation, with the highest value being 0.6% at 24 hours of fermentation time and the yeast mass of Saccharomyces cerevisiae 1.5 grams.